CLINICAL EFFECTIVENESS OF TRANS-ARTICULAR VERSUS RETRO-ARTICULAR DRILLING OF STABLE OSTEOCHONDRITIS DISSECANS OF THE KNEE: A, PROSPECTIVE RANDOMIZED CONTROLLED TRIAL BY THE ROCK STUDY GROUP. Issue 7 (30th July 2021) - Heyworth, Benton E.; Ganley, Theodore J.; Wall, Eric J.; Myer, Gregory D.; Nissen, Carl W.; Edmonds, Eric; Lyon, Roger M.; Chambers, Henry; Murnaghan, Lucas; Liotta, Elizabeth S.; Hergott, Katelyn A.; Milewski, Matthew D.; et al.
Background: The most common presentation of knee osteochondritis dissecans (OCD) is a stable lesion on the lateral aspect of the medial femoral condyle (MFC) in an adolescent or pre-adolescent athlete. Standard of care for conservative treatment, include activity modification and weight bearing protection. Failed conservative management often leads arthroscopy and drilling of the lesion. Two different primary drilling techniques have been utilized, but no prospective studies have compared their relative effectiveness. Hypothesis/Purpose: The study hypothesis was that trans-articular (TAD) and retro-articular drilling (RAD) would demonstrate similar rates of healing, times to return to sports, and patient-reported outcome scores (PROs). Methods: Skeletally immature (n=113) patients presenting with radiograph indicated stable OCD of the MFC who did not demonstrate healing despite a minimum of 3 months of non-operative treatment were prospectively enrolled and randomized to TAD or RAD, for which 17 surgeon-investigators (at 14 centers, representing all major regions in the U.S.). Serial radiographs were obtained every 6 weeks to assess healing, and PROs were obtained at 6 months, 12 months, and 24 months. Twelve patients were due to lesion instability detected at the time of surgery, Results: Ninety-one study subjects were included, consisting of 51 TAD and 40 RAD patients, with the two groups being of similar age (12.6 years vs. 11.9 years), sex distribution (45% vs. 27% female, p=0.081), and 2-year PRO response rate (both 90%). No significant difference between TAD and RAD was detected in follow-up Pedi-IKDC, Lysholm, Marx knee activity score, or KOOS QOL scores (Table 1). Revision/additional OCD surgery occurred in 10% of patients in RAD and 4% in TAD. 71% of TAD patients reached a 'healed' status at a mean of 1.15 years, compared with 58% RAD patients at a mean of 1.06 years. Conclusion: While both primary forms of OCD drilling (TAD and RAD) showed consistent post-operative healing, achieving a completely 'healed' status was often a more prolonged process, taking approximately 1 year, despite clinical improvement being achieved much sooner. While PROs were similar between drilling techniques, revision surgery rates were more than twice as common with RAD compared with TAD but the overall risk was low and the Absolute Risk was only 6%. :